Open Hearth Plant [copy negative] - William F. Cody:::::::::
Undated rendering of the Open Hearth Plant. It became the Kaiser Steel Plant in Fontana, California in 1943. Cody worked for Warren Engineers on Kaiser Steel Projects in 1943.